Analisi Kinerja Pegawai di Bagian Rekam Medis Rumah Sakit Umum Haji Medan - Susi Indah Roslia LumbanTobing; Beby Mashito; Irwan Nasution (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2022)
Management of medical record s in hospitals is to support the achievement of orderly administration in order to achieve the hospitals goals, namely improving the quality of health services that are affective and efficient in hopitals. Therefore, in the organization of medical records in every hospital. The sick must be admitted to the new general issued by the ministry of health and management. Medical records technically created by the hospital. The purpose of this research is to see. Employe performance in the medical records secition of the General Hospita Haji Medan. This research method used with indepth interviews, observation, documentation and data triangulations. Interview informants consist of medical record officers, doctors and nurses. From the research results, several files the medical records is not completely files in by the doctor, this causes the medical record file to the medical record unit.